CONTENT INSTRUCTOR AS SURROGATE ESL TEACHER: A SURVEY ON PERCEPTION, KNOWLEDGE AND WILLINGNESS - Abdullah, Ahmad Nazri (LLT Journal: A Journal on Language and Language Teaching, 2019)
In a normal university curriculum, students have to fulfil a minimum of 120 credit hours before they can graduate with a bachelor’s degree; of these, about 6 to 9 credit hours are usually reserved for ESL classes where students are taught the necessary language skills for use within the academic ambience or for future communication in the workplace. The amount of time reserved for language instruction might not be enough to really prepare students for the rigor of real-life academic and workplace demands. It is felt that the huge amount of time utilized for content-based subjects might serve as a valuable platform for language acquisition to take place if content instructors have the necessary language skills and if they can be made to view their role as surrogate ESL instructors. This paper sets out to gauge content instructors’ perception of their mastery of English, the role they can play as surrogate ESL instructors and their willingness to do so. A total of 24 content instructors from a technical university were selected as participants to provide the necessary information. Results indicate that most of the respondents perceived themselves as not apt to act as surrogate ESP instructors due to shortcomings in their language proficiency. DOI: doi.org/10.24071/llt.2019.220103